A New Efficient Ordering Scheme for Sphere Detection. (19th October 2011) - Haiyan, Cao; Jun, Li
Abstract : The decoding order has a deep impact in the complexity of sphere detection. A new ordering scheme for sphere detection is presented in this paper, which is based on SIC (serial interference canceling) and the gradient defined by the accumulated probability of the absolute difference between symbol element and the zero-forcing solution. The simulation results show that the proposed ordering scheme can achieve a significant complexity reduction, especially for high numbers of antennas and large constellation sizes in the low SNR region. Compared with sphere detection complexity under BSQR (balanced sorted QR) decomposition and GB (gradient-based) orderings atSNR = 5  dB, the average number of visited nodes under our proposed ordering is reduced by almost 30% and 33% in4 × 4 16QAM system and by almost 30% and 50% reduction in6 × 6 16QAM system, respectively. For4 × 4 64QAM system, almost 75% and 80% reduction atSNR = 0  dB and more than 40% and 50% reduction atSNR = 5  dB can be achieved, respectively.